1995
DOI: 10.4319/lo.1995.40.8.1430
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic and anaerobic decomposition of organic matter in marine sediment: Which is fastest?

Abstract: The enigma of aerobic vs. anaerobic decomposition in marine sediments was addressed by means of a thin-layer incubation technique. Two different 14C-labeled plant materials, aged diatoms (Skeletonema costatum) and fresh barley hay, were each mixed into intertidal sediment and spread in a 1.5-mm layer on the bottom of oxic and anoxic chambers. After a 27-d incubation, conditions in all chambers were switched from aerobic to anaerobic and vice versa for 11 d. Rates of 14C0, evolution in diatom chambers showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
240
0
5

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(257 citation statements)
references
References 23 publications
(22 reference statements)
12
240
0
5
Order By: Relevance
“…This agreed with Atkinson and Cairns (2001), who found that slower cattail decomposition rates were associated with longer HPs. They suggested that longer HPs created anaerobic conditions that slowed microbial efficiency, which agrees with other studies (Kristensen et al 1995;Scanlon & Moore 2000). Intermittent flooding may lead to higher decomposition rates for cattail than permanently flooded conditions (van der Valk et al 1991).…”
Section: Broadleaf Cattailsupporting
confidence: 80%
“…This agreed with Atkinson and Cairns (2001), who found that slower cattail decomposition rates were associated with longer HPs. They suggested that longer HPs created anaerobic conditions that slowed microbial efficiency, which agrees with other studies (Kristensen et al 1995;Scanlon & Moore 2000). Intermittent flooding may lead to higher decomposition rates for cattail than permanently flooded conditions (van der Valk et al 1991).…”
Section: Broadleaf Cattailsupporting
confidence: 80%
“…In contrast, a DOC accumulation is observed in the anoxic fluid mud (Fig. 8), similar to those reported in anoxic microcosm experiments (Otsuki and Hanya 1972a,b;Hansen and Blackburn 1991;Kristensen et al 1995;Andersen 1996). This DOC supply can be attributed to both desorption processes (Keil et al 1994), because of surface competition and rapid pH change (Morel et al 1991), and to the death of aerobic bacteria.…”
Section: Stoichiometry Of Early Diagenesis and Carbonate Dissolution mentioning
confidence: 47%
“…Because fluid mud preferentially exists during low river discharge periods, oxic/anoxic oscillation occurrence has to be relativized according to the season. Anaerobic mineralization, which transforms refractory POM slower than aerobic decomposition (Kristensen et al 1995), is restricted in time because periodic massive resuspensions occur. In contrast, a DOC accumulation is observed in the anoxic fluid mud (Fig.…”
Section: Stoichiometry Of Early Diagenesis and Carbonate Dissolution mentioning
confidence: 99%
“…The low DO in the waste sites is associated with increased decomposition of organic matter which requires oxygen especially during aerobic decomposition. According to Kristensen et al [47], oxygen plays two important functions during the degradation of organic matter, i.e. is a terminal electron acceptor for electrons released during oxidation of organic carbon and is a reactant in the oxygenase catalyzed primary attack on the substrate molecules.…”
Section: Dissolved Oxygen (Do)mentioning
confidence: 99%